Electrocardiographic Patterns of Ventricular Arrhythmias in Arrhythmogenic Right Ventricular Dysplasia/Cardiomyopathy - Hoffmayer, Kurt; Scheinman, Melvin M. (Frontiers in Physiology, 2012)
Ventricular arrhythmias in patients with ARVD/C are common. Differentiation between idiopathic ventricular tachycardia and arrhythmogenic right ventricular dysplasia is of utmost importance. Baseline sinus rhythm electrocardiography as well as electrocardiographic differences during ventricular arrhythmias (VT or PVCs) can be helpful in differentiating the two disease states. The pathological fibrofatty myocyte replacement in ARVD/C as well as ventricular arrhythmia origin are likely responsible for these differences.